Atividade antimicrobiana de extratos brutos de Petiveria alliacea L. - Guedes, Rodrigo C. M.; Nogueira, Natalia G. P.; Fusco-Almeida, Ana M.; Souza, Claudia R. F.; Oliveira, Wanderley P. (Colegio Farmaceuticos Provincia de Buenos Aires, 2009)
"Antimicrobial activity of crude extratcs of Petiveria alliacea L.". Petiveria alliacea L. (Phytolaccacea) is an herbaceous plant of great importance in traditional medicine. This species have been widely used in several applications such as antirheumatic, anticarcinogenic, anti-flu, antitussive, analgesic, insecticidal, acaricidal, as well as bactericide and fungicide. Currently, the pathogenic microorganisms are acquiring resistence against the traditional antibiotics, and the search for new herbal antimicrobial agents has been intensified. The objective of this study was to evaluate the antifungal and antibacterial activity of several leaf crude extracts of P. alliacea against several strains of bacterias and yeasts namely Bacilus subtilis, Pseudomonas aeruginosa, Escherichia coli, Streptococcus mutans, Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Candida parapsilosis, Candida kefyr and Candida albicans, using microdilution method. Promising results were observed for the 70% v/v ethanolic extract which presented minimum inhibitory concentration (MIC) from 250 to 760 mu g/mL for yeast. For the bacteria strains tested the MIC ranged between 240 to 3960 mu g/mL, depending of the extractive solution tested.
Antimicrobial activity of crude extratcs of Petiveria alliacea L.
Keywords: Crude extracts; Antimicrobial; Petiveria alliacea